Learning Identity A Sociocultural Perspective - Hyewon Park (Adult Education Research Conference, 2015)
This study examines the sociocultural perspective as the initial step to discovering an appropriate theoretical framework for describing how people learn identity. By illustrating the relation between the sociocultural perspective and identity, it suggests implications to overcome the limitations of existing adult learning studies to understand identity construction.
Keywords: identity construction; learning identity; sociocultural perspective